The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1111/j.1365-2265.2005.02261.x
|View full text |Cite
|
Sign up to set email alerts
|

The peroxisome proliferator activated receptor gamma Pro12Ala polymorphism is associated with a lower hirsutism score and increased insulin sensitivity in women with polycystic ovary syndrome

Abstract: The Pro12Ala polymorphism of the PPARgamma gene is associated with increased insulin sensitivity and lower hirsutism scores in PCOS women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
53
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 59 publications
11
53
5
Order By: Relevance
“…Whereas most studies (9)(10)(11)(12)14,15), present study included, reported no association between Pro12Ala genotype and PCOS diagnosis, a few reported that the Pro12Ala G allele was significantly less frequent in PCOS versus control women (13,16). Additionally, some studies reported significant increases in insulin sensitivity (decreased HOMA-IR) and decreases in fasting insulin and glucose levels (8-10) and lower hirsutism score (9) in PCOS women with the Pro12Ala G allele; whereas others (7,11,14), including this study, reported no association with fasting glucose and insulin or changes in HOMA-IR in those with PCOS. Only a subset of the subjects in our study was phenotyped for insulin-related traits, which may explain why we did not observe association with these traits in subjects with PCOS; however, this subset was still greater in number than each of the reports that did find an effect of Pro12Ala on insulin-related traits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas most studies (9)(10)(11)(12)14,15), present study included, reported no association between Pro12Ala genotype and PCOS diagnosis, a few reported that the Pro12Ala G allele was significantly less frequent in PCOS versus control women (13,16). Additionally, some studies reported significant increases in insulin sensitivity (decreased HOMA-IR) and decreases in fasting insulin and glucose levels (8-10) and lower hirsutism score (9) in PCOS women with the Pro12Ala G allele; whereas others (7,11,14), including this study, reported no association with fasting glucose and insulin or changes in HOMA-IR in those with PCOS. Only a subset of the subjects in our study was phenotyped for insulin-related traits, which may explain why we did not observe association with these traits in subjects with PCOS; however, this subset was still greater in number than each of the reports that did find an effect of Pro12Ala on insulin-related traits.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a polymorphism in exon 2 of the PPARγ2 isoform, resulting in a Pro12Ala substitution, influences the risk of type 2 diabetes with the rarer Ala allele associated with a lower incidence of diabetes (6). Several small studies have looked at the effects of the Pro12Ala and a silent exon 6 polymorphism (His447His) in association with PCOS, though they have produced conflicting results (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). To better understand the role of these polymorphisms in PCOS, we examined the Pro12Ala and silent exon 6 polymorphism in a cohort of 285 women with PCOS and 187 controls, the largest sample size of all published reports of PPARG in PCOS to date.…”
mentioning
confidence: 99%
“…It is well established that Ala allele, enhances insulin sensitivity and protects against development of T2DM [28]. Increased insulin sensitivity, decreased fasting insulin levels, HOMA-IR, [13,14,17,30,34] basal metabolic rate [16] and increased HDL-C levels [4] were observed in women with PCOS who were carriers of Ala alleles. Consistently we too observed that the variant genotype carriers had significantly lower 2 h glucose levels than wild genotype carriers in PCOS group but not in controls.…”
Section: Association Of Pparγ Pro12ala C/g Polymorphism With Pcos Andmentioning
confidence: 99%
“…However, in our study with increased sample size of PCOS women (n=450) and controls (n=300), a significant difference in both allelic and genotypic frequency were found; and further logistic regression analysis also revealed a stronger association of Pro12Ala polymorphism with reduced susceptibility to PCOS. Other studies with Italian [20,21], German [13], Chinese [32], Caucasian [1], Korean [4], Greek [5,33], Spanish [23] and Polish [3] women with PCOS failed to find any such association. It is well established that Ala allele, enhances insulin sensitivity and protects against development of T2DM [28].…”
Section: Association Of Pparγ Pro12ala C/g Polymorphism With Pcos Andmentioning
confidence: 99%
“…Associations of PCOS with mutations in a variety of candidate genes involved in pathways regulating steroid hormone synthesis (2,3) or insulin metabolism have been analyzed, without evidence of a single common defect. In women with PCOS, the impairment of insulin metabolism is thought to be influenced by both environmental (4) and genetic factors (5,6). Recently published studies from the Czech Republic (7) and Finland (8) have shown that insulin resistance and metabolic abnormalities are related to obesity rather than to PCOS per se.…”
Section: Introductionmentioning
confidence: 99%